Evaluation of The Performance of Learning Management System Using IS Success Model - Reni Haerani; Feby Charlos; Angga Pramadjaya (Applied Information System and Management (AISM), 2026)
Learning Management Systems (LMSs) have become a crucial element in digital learning at universities. However, not all LMSs demonstrate optimal implementation results. The urgency of this study arises from the need to ensure that the implemented LMS truly has a positive impact on the educational process, enhances the effectiveness of learning interactions, and increases user satisfaction. This study aimed to assess the effectiveness of LMS using the Information System Success Model (ISSM) proposed by Delone and McLean through a quantitative Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The variables analyzed included system quality, information quality, service quality, user satisfaction, system usage, and net benefits. The study's population comprised 548 LMS users from universities in Banten Province, including instructors and students who were active in the previous semester. Data were collected through questionnaires distributed via Google Forms and analyzed descriptively and quantitatively using SmartPLS 3.0 software to test the outer and inner models. The results of the study revealed that of the 10 hypotheses tested, 6 were accepted and 4 were rejected. The main findings indicate that system quality and service quality have a positive impact on intention to use and user satisfaction. These findings provide practical contributions for LMS managers in formulating steps to improve system quality, as well as theoretical contributions in developing models to evaluate the success of information systems in education.